Controversies when using mechanical ventilation in obese patients with and without acute distress respiratory syndrome. (4th May 2019) - Bonatti, Giulia; Robba, Chiara; Ball, Lorenzo; Silva, Pedro Leme; Rocco, Patricia Rieken Macêdo; Pelosi, Paolo
ABSTRACT: Introduction : As the prevalence of obesity increases, so does the number of obese patients undergoing surgical procedures and being admitted into intensive care units. Obesity per se is associated with reduced lung volume. The combination of general anaesthesia and supine positioning involved in most surgeries causes further reductions in lung volumes, thus resulting in alveolar collapse, decreased lung compliance, increased airway resistance, and hypoxemia. These complications can be amplified by common obesity-related comorbidities. In otherwise healthy obese patients, mechanical ventilation strategies should be optimised to prevent lung damage; in those with acute distress respiratory syndrome (ARDS), strategies should seek to mitigate further lung damage. Areas covered : This review discusses non-invasive and invasive mechanical ventilation strategies for surgical and critically ill adult obese patients with and without ARDS and proposes practical clinical insights to be implemented at bedside both in the operating theatre and in intensive care units. Expert opinion : Large multicentre trials on respiratory management of obese patients are required. Although the indication of lung protective ventilation with low tidal volume is apparently translated to obese patients, optimal PEEP level and recruitment manoeuvres remain controversial. The use of non-invasive respiratory support after extubation must be considered in individual cases.